2018
DOI: 10.1177/1028315318762524
|View full text |Cite
|
Sign up to set email alerts
|

9/11 and International Student Visa Issuance

Abstract: International student migration to the United States markedly dropped after the September 11, 2001, attacks. Considering the interaction of immigration policy and student agency, this study examines how student visa issuances changed after 9/11 to determine whether there were significant changes to international student flows to the United States. Nonimmigrant visa data from the U.S. Department of State annual Report of the Visa Office from 1997 to 2006 were analyzed. Results show that while there was no initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The primary changes to U.S. higher education for international students revolve around the 2016 election of Donald Trump and the accompanying increase in visa scrutiny (Chen et al, 2019;Hefner-Babb & Khoshlessan, 2018). Practical challenges (such as securing legal immigration status) have impacted international student recruitment since the post-9/11 period (Johnson, 2018), a trend that has continued since 2016 (Chen et al, 2019;Hefner-Babb & Khoshlessan, 2018). While increasing legal barriers have a serious impact on international higher education, they do not relate directly to our dependent or independent variables; in our review of the literature, we found no evidence that post-2016 visa policy changes impact acculturative stress, self-esteem, English proficiency, social connectedness, or homesickness.…”
Section: Limitationsmentioning
confidence: 99%
“…The primary changes to U.S. higher education for international students revolve around the 2016 election of Donald Trump and the accompanying increase in visa scrutiny (Chen et al, 2019;Hefner-Babb & Khoshlessan, 2018). Practical challenges (such as securing legal immigration status) have impacted international student recruitment since the post-9/11 period (Johnson, 2018), a trend that has continued since 2016 (Chen et al, 2019;Hefner-Babb & Khoshlessan, 2018). While increasing legal barriers have a serious impact on international higher education, they do not relate directly to our dependent or independent variables; in our review of the literature, we found no evidence that post-2016 visa policy changes impact acculturative stress, self-esteem, English proficiency, social connectedness, or homesickness.…”
Section: Limitationsmentioning
confidence: 99%
“…Following the 9/11 terrorist attacks, international students, (im)migrants and even Americans, especially those perceived to be Muslims, Arabs, and South Asians (Arnone, 2003;Basu, 2016;Farber, 2007), were labeled as threats to U.S. national security, guerillas, and terrorists in the making (Johnson, 2018;Urias & Yeakey, 2005). Likewise, Journal of Postsecondary Student Success amid COVID-19, Asians-a particular subset of both the general U.S. population and, even narrower, international students-were targeted and stigmatized as their ethnic identities became synonymous with the newly discovered virus (Cheung et al, 2020;Tavernise & Oppel Jr., 2020).…”
Section: Discussion Multiple Marginalized Identities Lead To a 'Double Whammy' For International Studentsmentioning
confidence: 99%
“…Many Americans' views of (im)migrants had changed for the worse and were further aggravated when generalized claims that the hijackers entered the U.S. on student visas surfaced, prompting stricter governance over international student migration. America's change of heart manifested in the development and implementation of restrictive systems and policies meant to target migrants (Johnson, 2018). These include the Student and Exchange Visitor Information System (SEVIS), the Uniting and Strengthening America by Providing Appropriate Tools Required to Intercept and Obstruct Terrorism laws, the Enhanced Border Security and Visa Entry Reform Act of 2001, and the National Security Entry-Exit Registration System, etc.…”
Section: /11: the Demonization Of International Studentsmentioning
confidence: 99%
See 1 more Smart Citation